Novel Angiotensin-I Converting Enzyme Inhibitory Peptides Isolated From Rice Wine Lees: Purification, Characterization, and Structure-Activity Relationship - He, Zeqi; Liu, Guo; Qiao, Zijiao; Cao, Yong; Song, Mingyue (Frontiers in Nutrition, 2021)
The bioactive peptides that can inhibit angiotensin-I converting enzyme (ACE, EC. 3. 4.15.1) are considered as possible cures of hypertension. Food-derived angiotensin-I converting enzyme inhibitory (ACEi) peptides have gained more attention because of their reduced side effects. In this study, we reported the method for purifying ACEi peptides from the lees of traditional Chinese rice wine and evaluated the product's biochemical properties. After three steps of reversed-phase high-performance liquid chromatography (RP-HPLC), for the first time, we isolated, purified, and identified two novel peptides: LIIPQH and LIIPEH, both of which showed strong ACEi activity (IC50-values of 120.10 ± 9.31 and 60.49±5.78 μg/ml, respectively). They were further categorized as mixed-type ACE inhibitors and were stable against both ACE and gastrointestinal enzymes during in vitro digestion. Together, these results suggest that the rice wine lees that produced as a by-product during rice wine production can be utilized in various fields related to functional foods and antihypertensive medicine.